(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
The main aim of the paper is to present and explain the complexity of the deep but hidden conflict between the ‘top’ and the ‘bottom’ that is currently taking place in many theatre institutions in Poland, including puppet theatres. Since 1989, Polish repertory theatres have been continually changing from the old, highly hierarchical Fordist mode of production to the new, flexible post-Fordist mode, which is characteristic for cognitive capitalism and alternative, neo-avant-garde theatre. These organisational changes and some new aesthetic trends are leading to the extinction of theatre craft, as the work of craftsmen is increasingly outsourced or replaced by ready-made objects. This paper presents the results of qualitative field research conducted at six Polish puppet theatres, each with a different range, including interviews with craftsmen, in order to examine the economical, technological and aesthetic decisions that cause dysfunctions and exacerbate the dying-off of backstage theatre professions.